Recurring Facial Erythema in an Infant - Sam Hassan; Mary Jacqueline Saviour (Case Reports in Pediatrics)
Causes of facial rashes and erythema in infants are many but rarely only happen during feeding times which are commonly and sometimes wrongly attributed to food allergy. There is a rare condition called Auriculotemporal nerve syndrome that is characterized by recurrent episodes of gustatory facial flushing and sweating along the cutaneous distribution of Auriculotemporal nerve: the so-called Frey syndrome. This condition is most frequently observed in adults usually after parotid surgery. It is rare in children and is mostly attributed to forceps assisted delivery. It can also be misinterpreted as food allergy. Here we report a case of an infant with Frey syndrome without any history of perinatal trauma, which was considered initially as food allergy and highlights the importance of distinguishing it from food allergy.